A Small Square Monopole Ultra-wideband Antenna with Band Stop Behavior - Pannu, Preeti; K. Pandey, Manoj (International Journal of Engineering and Technology, 2018)
A monopole antenna with a simple structure, planar geometry, and a small square size is proposed, in this paper. The proposed antenna structure consists of the slot with I-shaped geometry in the radiating patch surrounded by a C-geometry slot. Further, the structure contains a parasitic I-shaped element in the square radiating patch. The embedded slot with C-shaped geometry and parasitic I-shaped element accounts for the dual-band notch nature in the proposed antenna structure. The simulated and measured results are compared for the proposed antenna structure, which is in good agreement and also, band rejection capabilities of the proposed antenna are investigated.Â Â